Digital-Based Business Model Transformation of MSMEs: A Qualitative Study of Business Actors in East Lombok - Khalik, Abdul; Habib, M. Alfan (Dinasti International Journal of Digital Business Management, 2025)
Digital transformation has become a strategic necessity for Micro, Small, and Medium Enterprises (MSMEs) in responding to increasingly dynamic market conditions and competitive business environments. The rapid development of digital technologies, such as social media, online marketplaces, and digital payment systems, has driven fundamental changes in how MSMEs design and operate their business models. This study aims to analyze the process of digital-based business model transformation and to explore the experiences, strategies, and challenges faced by MSME actors in East Lombok Regency. This research employs a qualitative approach using a case study method, with data collected through in-depth interviews with MSME owners who have adopted digital technologies in their business activities. The findings indicate that digital transformation affects several key components of the business model, including value proposition, distribution channels, customer relationships, and cost and revenue structures. Digitalization enables MSMEs to expand market reach and improve operational efficiency; however, it also presents challenges related to digital literacy, infrastructure limitations, and human resource adaptability. This study contributes to the literature on digital business management and provides practical implications for policymakers and stakeholders in designing contextual digital empowerment strategies for MSMEs at the regional level.